Մերձաւոր Արեւելքի Հայ աւետարանական եկեղեցիներու միութեան վերականգնումը. 1924ի յետեղեռնեան Ա. համաժողովը եւ ցանկը' 1924-2024 համաժողովներու - Քասունի, Երուանդ հ., 1937- [հիմնադիր խմբագիր՝ 1970-1984]; Կռանեան, Անդրանիկ ծ. վրդ., 1929-2017 [1991-2017]; Տագէսեան, Անդրանիկ, 1960- [2018-] (տպ. Atlas)
In 2024 the Union of Armenian Evangelical Churches in the Near East (UAECNE) convened its 77th annual conference in Lebanon and celebrated its 100th anniversary. Back in 1924, after the Armenian Genocide and the second exile of the Armenians from Western Armenia, Cilicia and neighboring areas, surviving pastors of the Armenian Evangelical Churches of Cilicia and the environs gathered in Aleppo to restore the institution of the Union that existed in Cilicia, organize the newly formed Armenian Evangelical churches in Syria, Lebanon, Cyprus and the Middle East Arab countries and formalize them in a new Union which would have elements from the Cilician Union as well as new constituents. In this regard, UAECNE was both a continuation of past Armenian Evangelical traditions as well as an institutionalization of new developments with the church congregations.
Keywords: Հայ աւետարանական եկեղեցի; Մերձաւոր Արեւելք